Long‐term (5‐year) clinical evaluation of the Resolute zotarolimus‐eluting coronary stent: The RESOLUTE US clinical trial. Issue 6 (13th July 2019) - Kirtane, Ajay J.; Yeung, Alan C.; Ball, Michael; Carr, Jeffrey; O'Shaughnessy, Charles; Mauri, Laura; Liu, Minglei; Leon, Martin B.
Abstract: Objectives: To assess the long‐term safety and efficacy of the Resolute zotarolimus‐eluting stent (R‐ZES). Background: The R‐ZES has been associated with low rates of adverse events over short‐intermediate term follow‐up. However, reliable assessment of the safety and efficacy of any implanted device requires long‐term evaluation. Methods: The RESOLUTE US trial was a prospective, observational study conducted at 116 U.S. sites and enrolled patients with de novo coronary lesions. Patients were followed clinically for 5 years with independent event adjudication and data monitoring. Results: A total of 1, 402 patients (1, 573 lesions) were enrolled; 34% had diabetes mellitus and 75% had ACC type B2/C lesions. The 5‐year rate of target lesion failure (TLF) was 12.3%, target lesion revascularization was 6.5%, target vessel myocardial infarction was 3.2%, and cardiac death was 4.1%. Dual antiplatelet therapy usage was 94% at 1 year and 47% at 5 years, with a 0.1% and 0.5% respective incidence of definite or probable stent thrombosis. The 5‐year rate of TLF was 16.9% among patients with diabetes mellitus and 14.7% in patients with at least one small (≤2.5 mm) vessel treated. Covariates independently associated with 5‐year TLF in multivariable analysis included diabetes mellitus (odds ratio [OR] 1.89, p  < .001), prior coronary artery bypass grafting (OR 2.28, p  < .001), prior myocardial infarction (OR 1.85, p = .002), and smaller reference vessel diameter (OR 1.75, p = .004). Conclusions: Results from the fully adjudicated and monitored RESOLUTE US trial demonstrate long‐term 5‐year safety and efficacy of the R‐ZES stent among a relatively low‐risk population of patients, including a 0.5% rate of stent thrombosis at 5 years.